If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -8 = 5(x + 4) Reorder the terms: -8 + x = 5(x + 4) Reorder the terms: -8 + x = 5(4 + x) -8 + x = (4 * 5 + x * 5) -8 + x = (20 + 5x) Solving -8 + x = 20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -8 + x + -5x = 20 + 5x + -5x Combine like terms: x + -5x = -4x -8 + -4x = 20 + 5x + -5x Combine like terms: 5x + -5x = 0 -8 + -4x = 20 + 0 -8 + -4x = 20 Add '8' to each side of the equation. -8 + 8 + -4x = 20 + 8 Combine like terms: -8 + 8 = 0 0 + -4x = 20 + 8 -4x = 20 + 8 Combine like terms: 20 + 8 = 28 -4x = 28 Divide each side by '-4'. x = -7 Simplifying x = -7
| (72+x)/5=20 | | -6(3x-8)= | | 9a+6=(a+4) | | (x-4)=1 | | 5.8+(-2.5)= | | 3x+3+4x=7x-2+2x+4+7x-2 | | 17=3(p-5) | | 2y+4x=8x+-2 | | 2x/x+4=8/9 | | 2x+7=3x+4 | | 23+4x= | | 52=2x+y | | 7+4x=2x-11 | | 4/5=x/50 | | (2a)/3=-4.54545454545 | | 0.14(y-9)+0.10y=0.4y-0.01(60) | | 10-(-10)-7-5= | | 2c=5c+-19 | | 2(n+9)=3n-5 | | -3(7-4)= | | -3(7-4)= | | 5x+19+74= | | 9-y^2=14x+3 | | 6(9x-8)=47 | | d-17=45 | | -38+3r=8(4r+7)-7 | | 4x-9=7+9x+19 | | -32=-3+7x+3(x-2) | | -5x+7+3x=-1 | | 2(x-3)=5(2x+4) | | b+5=5/11 | | -x-47=31-7x |